Sacralization in the Mary Rose and Kronan assemblages: An inconsistently recorded anomaly. (1st April 2021) - Drew, Rose; Kjellström, Anna
Abstract: This study aims to promote consistent observations of sacralization, a relatively common form of lumbosacral transitional vertebrae (LSTV). Sacralization can inform on genetic affiliation. There are four types, ranging from enlarged transverse processes to bony ankylosis. Complete sacralization reportedly occurs in 1.5%–14% of archeological and modern populations, yet clinical studies can conflate types, resulting in rates as high as 46%. Archeologically obtained sacra and lower lumbar vertebrae from two historical shipwrecks (16th century English warship Mary Rose and 17th century Swedish warship Kronan) are compared via gross observation. These semi‐documented individuals, fit enough to be on a warship during battle, have a documented cause, manner, and date of death. The assemblages yield 120 sacra; complete sacralization is compared between the crews. Both crude and true prevalence of bony ankyloses are recorded with χ 2 analyses testing significance. Both samples have 16.7% true prevalence of complete sacralization, with 38.3% of Mary Rose sacra and 26.7% of Kronan sacra showing some variant of LSTV. It is possible the high rates of sacralization shown in both crews are related to the samples being drawn from similar populations: a Swedish clinical study finds a similar rate of 13.9% for "complete" sacralization. However, reported rates of less than 1.0% in other archeological samples suggest that true sacralization is inconsistently recognized. Finally, clinical and archeological studies either conflate all types or fail to state their diagnostic criteria, reducing the ability to accurately compare findings.